TIPI: TEV protease-mediated induction of protein instability - Taxis, Christof; Knop, Michael (Ubiquitin family modifiers and the proteasome, 2012)
Reverse genetics approaches require methods to inactivate a specific protein. One possibility is to modify the target protein with a degradation signal (degron). Degrons are short, transferable sequences that confer protein instability. They target proteins for degradation either constitutively or after activation, e.g., by phosphorylation, presence of a binding partner, or conformational rearrangements in the substrate. In this chapter, we describe a synthetic way to activate a degron. It employs the generation of an N-degron by cleavage of a substrate with the site-specific tobacco etch virus (TEV) protease. Subsequently, the substrate is targeted for degradation by the ubiquitin-proteasome system. This TEV protease-induced protein instability system provides a powerful approach to generate conditional mutants for synthetic biology or for the investigation of protein functions in a specific cellular context.
Gesehen am 10.08.2017